Predicting persistent back pain causing severe interference with daily activities among community-dwelling older adults: the OPAL cohort study - Esther Williamson; Maria T. Sanchez-Santos; Jeremy Fairbank; Lianne Wood; Sarah E. Lamb (BMC Geriatrics)
Abstract Background Many older adults experience disabling back and leg pain. This study aimed to identify factors associated with back pain causing severe interference with daily activities over 2 years. Methods Participants were 2,109 community-dwelling adults (aged 65–100 years; mean age 74.2 (SD 6.3)) enrolled in a prospective cohort study who reported back pain at baseline and provided back pain data at 2 years follow-up. Baseline data included demographics, socio-economic factors, back pain presentation and age-associated adverse health states (e.g. frailty, falls, walking confidence). At 2 years follow-up, we asked if they were currently experiencing back pain and if so, asked participants to rate how much their back pain interfered with their daily activities on a scale of 0–10. Severe back pain interference was defined by a rating of 7 or more. The association between baseline factors and severe back pain interference at two years was assessed using logistic regression models. Results At two years, 77% of participants (1,611/2,109) still reported back pain, 25% (544/2,083) also reported leg pain and 14% (227/1,611) reported severe back pain interference with activities. Improvements in symptoms were observed over the two years follow-up in 880/2,109 participants (41.7%), 41.2% (869/2,109) of participants report no change and worsening symptoms was reported by 17.1% (360/2109) of participants. After adjusting for back pain troublesomeness at baseline, factors associated with reporting severe interference were adequacy of income (careful with money [OR 1.91; 95% CI 1.19–3.06]; prefer not to say [OR 2.22; 95% CI 1.11–4.43]), low endorsement of exercise in later life (OR 1.18; 95% CI 1.02–1.37), neurogenic claudication symptoms (OR 1.68 (95% CI 1.15–2.46)], multisite pain (OR 1.13; 95% CI 1.02–1.24) and low walking confidence (OR 1.15; 95% CI 1.08–1.22). Conclusion After adjusting for baseline pain severity, we identified five factors that were associated with severe pain limitation at two years follow-up among a cohort of community dwelling older people reporting back and leg pain. These included other pain characteristics, walking confidence and attitude to activity in later life. We also identified a socioeconomic factor (perceived adequacy of income). Future research should focus on whether identifying individuals using these risk factors in order to intervene improves back pain outcomes for older people.